Návrh zlepšení marketingového mixu provozovny Ráj hadic - Svobodová, Denisa (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Diplomová práce se zabývá zhodnocením současného využití nástrojů marketingového mixu provozovny a následně stanovením návrhů zlepšení marketingového mixu provozovny Ráj hadic. Opatření by měla zvýšit povědomí zákazníků o provozovně a tím zvýšit počet zákazníků a zvýšení intenzity marketingových aktivit provozovny.

Diploma work deals with assessment of present usage of marketing mix instruments and subsequently setting of improving proposals of marketing mix of the shop Ráj hadic. This proceeding should increase awareness of customers about the shop and by that to raise a number of the customers and intentsity of its marketing activities.
Proposal of Marketing Mix Improvement of Shop Ráj hadic
Keywords: Marketing; marketingový mix; produkt; cena; distribuce; propagace; Marketing; marketing mix; product; price; place; promotion